Geometry concept on monument tugu malang city - Ning Tiyas, Yolanda Redita Ika; Zahbi, Ud’Hiyata; Afidatuzzaro, Nurul (International Journal on Teaching and Learning Mathematics, 2022)
This study aims to identify the concept of geometry contained in the monument of Malang City. This research is a qualitative research with ethnographic approach.  Data collection techniques used were observation and literature study. This study concluded that the Malang City monument has mathematical concepts that can be applied in learning activities, namely the concept of flat and spatial shapes.